2008
DOI: 10.1111/j.1472-765x.2007.02319.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a lectin from Eugenia uniflora L. seeds and its potential antibacterial activity

Abstract: Aims:  The aim of this work was to analyse the antimicrobial properties of a purified lectin from Eugenia uniflora L. seeds. Methods and Results:  The E. uniflora lectin (EuniSL) was isolated from the seed extract and purified by ion‐exchange chromatography in DEAE‐Sephadex with a purification factor of 11·68. The purified lectin showed a single band on denaturing electrophoresis, with a molecular mass of 67 kDa. EuniSL agglutinated rabbit and human erythrocytes with a higher specificity for rabbit erythrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 20 publications
8
40
0
7
Order By: Relevance
“…These concentrations were being enough to mediate an effective antimicrobial activity against Klebsiella pneumonia and Pseudomonas aeruginosa, Staphylococcus aureus and Candida albicans, respectively. The previous results matched with those obtained by Oliveira et al [7].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These concentrations were being enough to mediate an effective antimicrobial activity against Klebsiella pneumonia and Pseudomonas aeruginosa, Staphylococcus aureus and Candida albicans, respectively. The previous results matched with those obtained by Oliveira et al [7].…”
Section: Discussionsupporting
confidence: 82%
“…The binding capacity of lectins could be the cause of its biological activities against bacteria, fungi, viruses and tumor [7][8][9][10]. The interaction of lectin with teichoic and teichuronic acids, peptidoglycans and lipopolysaccharides present in bacterial cell walls are responsible for its antibacterial activity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the insoluble dietary fiber of pitanga seeds could be evaluated for use in human and/or animal nutrition. However, it is important to evaluate if the lectins recently described in pitanga seeds (OLIVEIRA et al, 2008) could be a limiting factor for this application. Table 2 presents the fatty acid composition of pitanga seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the essential oil from pitanga fruits contains β-ocimene (7.4%), α-selinene (7.2%), β-selinene (5.2%), germacrene B (7.2%) and hexadecanoic acid (11.7%) and was demonstrated to have an interesting antioxidant activity (MARIN et al, 2008). However, few studies were found on bioactive compounds from pitanga seeds (OLIVEIRA et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…cancer), including as main components of microarrays (Gemeiner et al 2009). Antimicrobial activity of lectins has been reported in the literature against fungi and bacteria (Oliveira et al 2008;Gomes et al 2013). The toxicity of lectins has also been studied ensuring their safe use in human health (Rolim et al 2011).…”
Section: Resultsmentioning
confidence: 99%